Serum Transferrin Receptor Assay in Iron-Deficiency Anemia and Anemia of Chronic Diseases - Fatin M. Al Sayes; Safa Y. Qusti; Mamdooh A. Gari; Manal A. Babaker (Journal of King Abdulaziz University: Medical Sciences, 2023)
Serum Transferrin Receptor is a biochemical parameter used for the detection of iron deficiency in situation where ferritin has limited diagnostic value. This study investigates the level and the significance of serum transferrin receptor among patients with iron deficiency anemia and anemia of chronic diseases at King Abdulaziz University Hospital in Jeddah, Saudi Arabia. All samples were collected from patients, ages ranged between 20-63 years, from May to December 2008. Seventy three control subjects (61 males and 12 females), plus 65 anemic patients were enrolled into this study, which was divided into two groups: 37 (3 males and 34 females) patients with iron deficiency anemia and 28 (15 males and 13 females) patients with anemia of chronic diseases. Anemia of chronic diseases patients, were divided into sub-categories of malignant diseases (n = 11), chronic inflammatory disease (infectious and non-infectious) (n = 9) and an end stage renal disease (n = 8). Complete blood counts, serum ferritin, serum iron, serum transferrin receptor and serum transferrin receptor/log ferritin were measured for these subjects. The mean results of the serum transferrin receptor concentration among control subject were 2.47 ± 0.62 µg/mL (range 1-3.65 µg/mL). All patients with iron deficiency anemia had an elevated serum transferrin receptor level (> 3.65 µg/mL); chronic diseases had normal levels of serum transferrin receptor; except 8. The higher value in these patients suggests the presence of concurrent iron deficiency. There were no significant differences in the mean of serum transferrin receptor concentration and sex in control subjects and two groups of patients. A significantly higher serum transferrin receptor/log ferritin was observed in iron deficiency anemia (9.33 ± 8.81) compared to control subjects (1.32 ± 0.39) and anemia of chronic diseases (1.35 ± 1.1). The mean of serum transferrin receptor concentration and serum transferrin receptor/log ferritin in anemia of chronic diseases were not significantly different from that of the control subjects. There was no significant differences between different causes of anemia of chronic diseases: malignant diseases, chronic inflammatory diseases (infectious and non-infectious) and end stage renal disease and mean serum transferrin receptor concentration (2.68 ± 1.80 µg/mL , 2.38 ± 1.39 µg/mL, and 2.71 ± 2.11 µg/mL, respectively). Therefore, using the serum transferrin receptor concentration is recommended to differentiate between simple iron deficiency anemia and anemia of chronic diseases, plus it is a very useful tool when anemia of chronic diseases coexists with iron deficiency anemia.